Duration of Heart Failure and Effect of Defibrillator Implantation in Patients With Nonischemic Systolic Heart Failure. (September 2019) - Elming, Marie Bayer; Thøgersen, Anna M.; Videbæk, Lars; Bruun, Niels E.; Eiskjær, Hans; Haarbo, Jens; Egstrup, Kenneth; Gustafsson, Finn; Hastrup Svendsen, Jesper; Høfsten, Dan E.; Pehrson, Steen; Nielsen, Jens C.; et al.
Abstract : Background: Patients with nonischemic systolic heart failure (HF) have increased risk of sudden cardiac death (SCD) and death from progressive pump failure. Whether the risk of SCD changes over time is unknown. We seek here to investigate the relation between duration of HF, mode of death, and effect of implantable cardioverter-defibrillator implantation. Methods and Results: We examined the risk of all-cause death and SCD according to the duration of HF among patients with nonischemic systolic HF enrolled in the DANISH (Danish Study to Assess the Efficacy of ICDs in Patients with Non-ischemic Systolic Heart Failure on Mortality). In all, 1116 patients were included. Patients were divided according to quartiles of HF duration (⩽8, 9⩽18, 19⩽65, and ≥66 months). Patients with the longest duration of HF were older, more often men, had more comorbidity, and more often received a cardiac resynchronization therapy device. Doubling of HF duration was an independent predictor of both all-cause mortality (hazard ratio [HR], 1.27; 95% CI, 1.17–1.38; P <0.0001), and SCD (HR, 1.29; 95% CI, 1.11–1.50; P =0.0007). The proportion of deaths caused by SCD was not different between HF quartiles ( P =0.91), and the effect of implantable cardioverter-defibrillator implantation on all-cause mortality was not modified by the duration of HF ( P =0.59). Conclusions: Duration of HF predicted both all-cause mortality and risk of SCD independently of other risk indicators. However, the proportion of death caused by SCD did not change with longer duration of HF, and the effect of implantable cardioverter-defibrillator was not modified by the duration of HF. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00542945. Abstract : Supplemental Digital Content is available in the text.